Pengaruh Kinerja Keuangan Terhadap Harga Saham pada Perusahaan Sektor Property dan Real Estate yang Terdaftar di BEI Periode 2019-2023 - Sulfiana Satar; Zulkifli Bokiu; Ayu Rakhma Wuryandini (GEMILANG: Jurnal Manajemen dan Akuntansi, 2025)
Property & real estate companies are one of the sectors in the capital market that also determine the success of the country's economy. However, in 2020 this sector experienced the deepest decline of 33.56% due to a decrease in people's purchasing power, which then had an impact on a decrease in sales, thus reducing the company's net profit. This resulted in a decrease in stock prices. This study aims to test the effect of return on assets (ROA) and debt to asset ratio (DAR) on stock prices. The stock price used is the closing price per year. This study uses 15 samples of property & real estate sub-sector companies listed on the Indonesia Stock Exchange (IDX) for the 2019-2023 period. The sampling method used in this study is the purposive sampling technique and the type of data used is secondary data. The data analysis method used is panel data regression analysis, using Eviews 12 software. The results of this study indicate that return on assets (ROA) has a positive and significant effect on stock prices. While the debt to asset ratio (DER) has a negative effect on stock prices. Simultaneously, return on assets (ROA) and debt to asset ratio (DAR) have an influence on stock prices in property & real estate sub-sector companies for the period 2019-2023.